Benefits and Challenges of ERP Implementation in Higher Education Institutions: A Systematic Literature Review - Sholeh, Moch. Badrus; Samodra, Renita Fauziah; Widodo, Aris Puji (Jurnal Sistem Informasi Bisnis, 2025)
This study aims to identify the benefits and challenges of Enterprise Resource Planning (ERP) implementation in higher education institutions through a Systematic Literature Review (SLR). Based on the analysis of 37 relevant articles, the findings show that ERP implementation provides significant benefits, such as reducing operational costs, increasing efficiency, and enhancing decision-making. However, challenges such as system complexity, resistance to change, and technological infrastructure limitations remain major obstacles. To address these challenges, increased training, coordination, and management support are required, along with adequate budget allocation. The findings of this study are expected to provide higher education management with insights into the importance of thorough planning in ERP implementation to achieve successful outcomes.